Triptolide Prevents Bone Destruction in the Collagen-Induced Arthritis Model of Rheumatoid Arthritis by Targeting RANKL/RANK/OPG Signal Pathway. (12th March 2013) - Liu, Chunfang; Zhang, Yanqiong; Kong, Xiangying; Zhu, Liuluan; Pang, Jian; Xu, Ying; Chen, Weiheng; Zhan, Hongsheng; Lu, Aiping; Lin, Na
Abstract : Focal bone destruction within inflamed joints is the most specific hallmark of rheumatoid arthritis (RA). Our previous study indicated that the therapeutic efficiency of triptolide in RA may be due partially to its chondroprotective and anti-inflammatory effects. However, its roles in bone destruction are still unclear. In this study, our data firstly showed the therapeutic effects of triptolide on severity of arthritis and arthritis progression in collagen-induced arthritis (CIA) mice. Then, by micro-CT quantification, triptolide treatment significantly increased bone mineral density, bone volume fraction, and trabecular thickness and decreased trabecular separation of inflamed joints. Interestingly, triptolide treatment could prevent the bone destruction by reducing the number of osteoclasts in inflamed joints, reducing the expression of receptor activator of NF- κ B (RANK) ligand (RANKL) and RANK, increasing the expression of osteoprotegerin (OPG), at both mRNA and protein levels, and decreasing the ratio of RANKL to OPG in sera and inflamed joints of CIA mice, which were further confirmed in the coculture system of human fibroblast-like synovial and peripheral blood mononuclear cells. These findings offer the convincing evidence for the first time that triptolide may attenuate RA partially by preventing the bone destruction and inhibit osteoclast formation by regulating RANKL/RANK/OPG signal pathway.